ChemInform Abstract: Development of a Generic Activation Mode: Nucleophilic α‐Substitution of Ketones via Oxy‐Allyl Cations. Issue 48 (26th November 2013) - Vander Wal, Mark N.; Dilger, Andreew K.; MacMillan, David W. C.
Abstract A mild method for the generation of intermediary oxy‐allyl cations, allowing for nucleophilic α‐functionalization of ketones is developed.